Analysis of Rectangular Reinforced Concrete Liquied Tanks by Using Yield Line Theory - Zandi, Yousef; Keivani, Afram (Civil and Sustainable Urban Engineering, 2021)
In the analysis of rectangular reinforced liquid storage tanks, a method assuming linear-elastic behavior for material can be used, i.e., the strip method, the moment coefficient method, the finite element method, etc. In the analysis of these types of tanks, tank walls can be considered as slabs. In this study, tank walls were analyzed as slabs subjected to hydrostatic loading; in the analysis, the yield line theory is used because it is more suitable for the linear inelastic behavior of reinforced concrete slabs than the ones based on the linear elastic theory. An iterative algorithm based on yield line theory is presented for the design of isotropically reinforced rectangular concrete slabs supported along all four edges. A computer program is coded which predicts the location of yield lines for the slabs depending upon certain parameters. As a result of this prediction, the manual design of such slabs can be significantly simplified by the use of the coefficient obtained by using the program. It was shown that the analytical computation of the ultimate moment per unit length requires the solution of a highly nonlinear system of equations. This difficulty was overcome by utilizing an iterative technique within the computer program. It also gives the value of the ultimate moment per unit length of the yield line.